Driving forces behind the development of the "Integrated Control and Prevention of Three Highs and Six Diseases" strategy for chronic disease management in Shandong province: a multiple streams framework-based analysis - Wenyu FAN; Yu ZHANG; Haipeng WANG; Cong QI; Gaohui ZHANG; Liangxia CHEN; Xiaopang RAO; Yang ZHAO (Zhongguo gonggong weisheng)
This study elucidates the evolutionary mechanism of the "Integrated Control and Prevention of Three Highs (high blood pressure/glucose/lipids) and Six Diseases (coronary heart disease, stroke, renal lesions, retinal lesions, peripheral neuropathy, and peripheral vascular lesions)" strategy for chronic disease management to explore its future development direction. This study uses the multiple streams framework (MSF) to analyze the influencing factors of the policy changes in the "Integrated Control and Prevention of Three Highs and Six Diseases" strategy and points out the necessity and rationality of this strategy. The study found that the emergence of chronic disease management problems, public sentiment, suggestions from experts and scholars, national governance philosophy, and the formulation of relevant policies all influence the development of chronic disease management policies. The effective confluence of the problem stream, policy stream, and political stream is the main reason for the emergence of the "Integrated Control and Prevention of Three Highs and Six Diseases" strategy. Under the guidance of the MSF, the "Integrated Control and Prevention of Three Highs and Six Diseases" strategy should be further optimized from the perspectives of problem, policy, and political perspectives and provide a reference for further improvement of chronic disease management policies.